Clitoral hemangioma - Rarest cause of clitoromegaly - Ashoka Nand Thakur (Wolters Kluwer Medknow Publications, 2022)
Clitoromegaly in female child is a rare condition. This is often associated with androgen excess in disorders of sexual differentiation usually congenital adrenal hyperplasia. Nonhormonal causes of clitoromegaly are rare and are commonly due to neurofibromatosis, epidermoid cyst, rhabdomyosarcoma, and very rarely hemangioma. Hemangioma is one of the common benign neoplasms of infancy, usually located in head, trunk, and extremities. We are reporting 4-month-old child with clitoromegaly with normal hormonal assay. Clitoromegaly was due to hemangioma. Histopathology of mass confirmed the diagnosis. Only five cases have been reported in literature till date.